The C‐terminal domains of the NMDA receptor: How intrinsically disordered tails affect signalling, plasticity and disease. (16th July 2020) - Warnet, Xavier L.; Bakke Krog, Helle; Sevillano‐Quispe, Oscar G.; Poulsen, Hanne; Kjaergaard, Magnus
Abstract: NMDA receptors are part of the ionotropic glutamate receptor family, and are crucial for neurotransmission and memory. At the cellular level, the effects of activating these receptors include long‐term potentiation (LTP) or depression (LTD). The NMDA receptor is a stringently gated cation channel permeable to Ca 2+, and it shares the molecular architecture of a tetrameric ligand‐gated ion channel with the other family members. Its subunits, however, have uniquely long cytoplasmic C‐terminal domains (CTDs). While the molecular gymnastics of the extracellular domains have been described in exquisite detail, much less is known about the structure and function of these CTDs. The CTDs vary dramatically in length and sequence between receptor subunits, but they all have a composition characteristic of intrinsically disordered proteins. The CTDs affect channel properties, trafficking and downstream signalling output from the receptor, and these functions are regulated by alternative splicing, protein–protein interactions, and post‐translational modifications such as phosphorylation and palmitoylation. Here, we review the roles of the CTDs in synaptic plasticity with a focus on biochemical mechanisms. In total, the CTDs play a multifaceted role as a modifier of channel function, a regulator of cellular location and abundance, and signalling scaffold control the downstream signalling output. Abstract : The C‐terminal domains of the NMDA receptor plays a crucial role in synaptic plasticity by coordinating receptor trafficking and downstream signalling. Here we review how intrinsically disordered tails regulate the receptor with a focus on describing molecular mechanisms.